2021
DOI: 10.1098/rsos.210567
|View full text |Cite
|
Sign up to set email alerts
|

A review of π-conjugated polymer-based nanocomposites for metal-ion batteries and supercapacitors

Abstract: Owing to their extraordinary properties of π-conjugated polymers (π-CPs), such as light weight, structural versatility, ease of synthesis and environmentally friendly nature, they have attracted considerable attention as electrode material for metal-ion batteries (MIBs) and supercapacitors (SCPs). Recently, researchers have focused on developing nanostructured π-CPs and their composites with metal oxides and carbon-based materials to enhance the energy density and capacitive performance of MIBs and SCPs. Also,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 144 publications
(237 reference statements)
0
17
0
Order By: Relevance
“…[1,2] These polymer materials also have extraordinary advantages of low cost, light weight, excellent structural stability, as well as diverse functionality. [3][4][5] Therefore, CP-based materials have been extensively studied in organic electronics in the past few decades, such as rechargeable batteries, [6][7][8][9][10] field-effect transistors, [11,12] light-emitting diodes, [13,14] photovoltaics (PVs), [15][16][17][18][19][20] photocatalysts, [21,22] electrochromic devices, [23,24] biosensors, [25,26] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] These polymer materials also have extraordinary advantages of low cost, light weight, excellent structural stability, as well as diverse functionality. [3][4][5] Therefore, CP-based materials have been extensively studied in organic electronics in the past few decades, such as rechargeable batteries, [6][7][8][9][10] field-effect transistors, [11,12] light-emitting diodes, [13,14] photovoltaics (PVs), [15][16][17][18][19][20] photocatalysts, [21,22] electrochromic devices, [23,24] biosensors, [25,26] and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Cross‐coupling methods which are the mostly applied techniques for COPs, require highly inert atmosphere and refluxing conditions [11] . Classical chemical polymerization methods for COPs involve the excess use of oxidizing metal salts which are hard to remove the trace amount that deteriorates the optoelectronic properties of the final polymer [12] . Electrochemical production of COPs avoids the use of any metal salts [13] .…”
Section: Introductionmentioning
confidence: 99%
“…[11] Classical chemical polymerization methods for COPs involve the excess use of oxidizing metal salts which are hard to remove the trace amount that deteriorates the optoelectronic properties of the final polymer. [12] Electrochemical production of COPs avoids the use of any metal salts. [13] However, it mainly suffers from the decrease of the efficiency of the electrode during polymerization reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers (CPs) have driven innovations in a variety of energy conversion and storage fields including organic photovoltaics (OPVs), 1,2 supercapacitors, 3 transistors, 2 thermoelectrics, 2 lithium ion batteries (LIBs), [3][4][5] and other metal cation battery systems. 3,4 Recently, CP research has increasingly focused on developing novel, simplified reaction schemes as an alternative to costly multi-step synthetic procedures with traditionally catalyzed crosscoupling reactions that may be difficult to implement at scale.…”
Section: Introductionmentioning
confidence: 99%
“…Conjugated polymers (CPs) have driven innovations in a variety of energy conversion and storage fields including organic photovoltaics (OPVs), 1,2 supercapacitors, 3 transistors, 2 thermoelectrics, 2 lithium ion batteries (LIBs), [3][4][5] and other metal cation battery systems. 3,4 Recently, CP research has increasingly focused on developing novel, simplified reaction schemes as an alternative to costly multi-step synthetic procedures with traditionally catalyzed crosscoupling reactions that may be difficult to implement at scale. 6 For example, previous reports have demonstrated that OPV cost scales directly with the number of synthetic steps, 7 and significant effort has been dedicated towards developing new, comparatively simple polymerization methods such as direct heteroarylation to produce conjugated polymers.…”
Section: Introductionmentioning
confidence: 99%